Evaluación preliminar del síndrome de disfunción cognitiva (SDC), en perros geriátricos en la clínica veterinaria UDLA mediante el uso del test DISHA - Caviedes Vergara, Oswaldo Arturo (2018)
The Cognitive Dysfunction Syndrome is a disease that affects canines in geriatric age altering their cognitive functions giving as a result the change between the relationship they have with the environment, which have similarity with Alzheimer is disease that occurs in humans. The present analysis was carried out in the period from March the 19th to April the 19th in all the geriatric patients who attended the America is University (UDLA) veterinary clinic in the city of Quito. The purpose of the study was to perform a preliminary evaluation of the Cognitive Dysfunction Syndrome by the application of the DISHA test, which analyzes changes on the behavior of canines from the perspective of the owners and addressed to dogs older than 7 years old. Sixty-one dogs participated on the evaluation, which forty-two were suitable for their owners to be tested. The data obtained was analyzed with the statistical program IBM SPSS Statistics Viewer, finding that from the total population of participants 16.6 percent did not present any alteration, 11.9 percent were diagnosed with mild degree, 23.8 percent with moderate degree, 26.2 percent with severe degree and 21.4 percent were strongly severe. Without positive association with the following variables: age, sex, weight and race since the result was not sufficient to find a relationship between the variables, however it was possible to prove the existence of alterations compatible with the Syndrome.